Experience of Pediatric Teratomas in Uncommon Sites in a Tertiary Centre - Chhanda Das; Madhumita Mukhopadhyay; Ankita Pranab Mandal; Biswanath Mukhopadhyay; Ashis Kumar Saha (Current Progress in Medicine and Medical Research Vol. 6, 2023)
Introduction: In pediatric surgical practice, teratomas in gonads and sacrococcygeal areas are relatively common neoplasms. Teratomas in extragonadal sites are rare, with diverse clinical features and variable biological behavior. Aim: The aim of the study was to observe the prevalence of pediatric teratomas in atypical sites, clinical presentation, and histological variation. Materials and Methods: This prospective observational study was carried out for 5 years from January 2017 to December 2022 in the Department of Pathology in a tertiary care hospital in collaboration with Department of Pediatric Surgery. 119 cases of pediatric teratoma were analyzed in the Department of Pathology of which 42 cases were at atypical sites. Clinical parameters like history taking and relevant clinical examination, imaging studies and routine investigations were all done according to the proforma. The excised specimens were received. Sections from various areas of the tumor was submitted. The paraffin embedded tissue blocks were subsequently stained for H&E followed by histopathological reporting. Results and Analysis: A total of 119 cases of pediatric teratomas were recorded, of which, 42 cases were teratoma of atypical site. This included, retroperitoneal teratoma (14 cases), sacrococcygeal teratoma (13 cases), gastric teratoma (3 cases), cervical teratoma (1 case), pulmonary teratoma (1 case), adrenal teratoma (2 cases), floor of the mouth (1 case), pancreas (1 case), kidney (2 cases), abdominal wall (1 case), oral cavity (2 cases) and mesentery (1 case). Retroperitoneum and sacrococcyx were the commonest rare sites. Conclusion: Meticulous search for the immature or malignant component should be instituted as it helps in therapeutic decisions. Early diagnosis influences clinical decision and management, providing a better outcome. Continued follow-up (with alpha-fetoprotein and radiology) to rule out recurrence. More effective antenatal screening, for early diagnosis and management, to reduce the risk of malignant transformation, hence better prognosis.